Energy efficiency through lighting systems : a case study at the Agriculture Faculty Building, Kano University of Science and Technology, Wudil, Kano, Nigeria - Abdullahi, Abdurrahman Yusuf (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
In Nigeria, there is an urgent need for energy demand as the population increases. This also results the increasing demand of lighting energy. Due to this, the lighting energy needs to have energy savings, cost savings, and reduction of greenhouse gas emission, which affects global warming. The literature reveals that the commercial buildings like universities consume a significant amount of lighting energy and this makes it as an avenue of interest in reducing lighting energy consumption. This research was aimed at exploring the use of lighting system as the way of improving energy efficiency at the Agriculture Faculty Building (AFB) Kano University of Science and Technology (KUST), Wudil, Kano, Nigeria. Three lighting systems FLT8 (usually used), FLT5 and LED (improved) were employed to identify which of them would be the most suitable for improving energy efficiency. There were three main methods followed, which are the calculation of energy usage was conducted to determine the energy consumption of each lighting system with helped off the lumen method to find the number of fittings in AFB. Meanwhile, the return on investment was obtained by using simple payback period. The findings from this study show that the FLT5 and LED lamps save more energy as compared to the FLT8. The FLT5 saves 41% of energy consumed while the LED saves 44% of the energy consumed and both reduced the CO2 emission by more than 2 Metric tons. The findings also reached that in terms of the return on investment (ROI), although the LED can save more energy, its ROI is 12 years compared to 2 years of FLT5. Therefore, the FLT5 proved a more efficient choice to LED. Moreover, in the thirty years, projection, LED has more benefits. This helps the university and the world over in saving the energy, cost and reducing of GHG emission effects.